THE USE OF QUANTUM TEACHING MODELS ON EQUILIBRUM CHEMISTRY FOR ELEVEN-GRADE STUDENTS IN SENIOR HIGH SCHOOLS OF 14 PALEMBANG - Oktasari, Citra; Prisciliyo, G; Rachman, F Abd; Hartono, Hartono (Department of Integrated Science, Faculty of Mathematics and Natural Sciences, Universitas Negeri Semarang in Collaboration with Perkumpulan Pendidikan IPA Indonesia, 2019)
The purpose of this research is to determine the use of quantum teaching models on equilibrium chemistry to improve chemistry learning process in senior high schools 14 of Palembang. The quantum teaching model is one of the guidelines in planning and implementing learning that can improve the teaching and learning process in a class consisted of six phase i.e Grow, Natural, Name, Demonstrate, Repeat and Celebrate. The subject of this research was 40 eleven-grade students. This research was conducted for 3 cycles. The averages of students learning outcomes before treatment (T0) was 51.82 with percentage of learning completeness was 10%. The average of students’ learning outcomes in first cycle (T1) was 68.4 with percentage of learning completeness was 47.37%. The average of students learning outcomes in the second cycle (T2) was 78.9 with the percentage of learning completeness was 78.9%. The average of the students’ learning outcomes in the third cycle (T3) was 84.4 with the percentage of learning completeness was 86.84%. Based on observe to students activity, quantum teaching can improve students activity, that is in the first cycle was 50.64%, the second cycle was 63.03% and 73.76% was for the third cycle.